Geriatric outpatient healthcare: hierarchical demand structuring - Lourenço, Roberto Alves; Martins, Cláudia de Souza Ferreira; Sanchez, Maria Angélica S; Veras, Renato Peixoto (Revista de Saúde Pública, 2005)
In Brazil, the rapid growth of the elderly population has been causing a great impact on the healthcare system, with increased costs and service utilization. The inefficiency of traditional models for geriatric healthcare has made it essential to change the healthcare concepts for this population. This can take place through the development of new healthcare models that include the means to identify, assess and treat elderly patients with a variety of morbid and functional conditions, and which can be applied diverse healthcare scenarios. An outpatient model is proposed, with two stages that differ in the depth and coverage of their actions. These stages are organized as increasing levels of complexity and are capable of selecting subgroups of individuals that, because of their risk characteristics, should follow different paths through the healthcare structure. This paper discusses the first stage of this model, which involves risk identification among large groups of elderly people, by means of structuring a hierarchical flow of actions and using assessment tools of adequate sensitivity and specificity. Individuals aged 65 years or over who are detected through walk-in outpatient consultation, home visits or telephone interview are classified using a rapid screening risk evaluation instrument composed of eight items. Depending upon the level of risk presented, the individual will either be referred to another level of functional evaluation (medium-high and high risk levels), or to normal clinical care and old people's community centers (low and medium risk levels). The second stage will be the subject of a subsequent paper.